PRAGMATIC CRITICISM OF THE KARMAN’S INNER STRUGGLE ON KUBAH NOVEL BY AHMAD TOHARI (PRAGMATIK KRITIS PERJUANGAN BATIN KARMAN DALAM NOVEL KUBAH OLEH AHMAD TOHARI) - Ikin Syamsudin Adeani; Cikal Yulianti (Jurnal Gramatika, 2021)
The understanding of material values can influence the strength of one's faith and belief in a situationthat can cause someone to no longer acknowledge the existence of God. The purpose of this research is to describe and interpret the inner struggle of the main character, Karman, in the novel Kubah by Ahmad Tohari. This type of research method used is a qualitative descriptive method. The data obtainedin the form of written words related to the structure and religious values contained in the novel Kubah by Ahmad Tohari. Sources of data in this study are the novel Kubah by Ahmad Tohari and other referencesfrom other books and articles that are relevant to the research. The data collection technique used in thisresearch is the documentation technique. The inner struggle with little faith remaining describes how a central figure returns to his original beliefs and doubts whether the main character will be acceptedin his community or not. Analysis and intrinsic elements of religious value contained in the novel can be identified from the behavior of the characters in the story.